INKLUSIVITAS DAN TOLERANSI DI SEKOLAH DASAR (Studi Kasus di SDI Logo, Manggarai Timur NTT) - Edu, Ambros Leonangung; Maksum, Arifin; Nurhasanah, Nina; Wahyu, Yuliana (Jurnal Pendidikan dan Kebudayaan Missio, 2025)
The SDI Logo School in East Manggarai Regency, NTT Province, serves as an example of tolerance practices in the primary education environment, where values of tolerance are well-preserved and cultivated. This study aims to explore the dynamics of interfaith tolerance at SDI Logo, with a focus on the religious social interactions of students. The methods used in this research include questionnaires, interviews, and document analysis. Questionnaires were employed to measure the perceptions of teachers and the school principal regarding tolerance, while interviews were conducted to confirm the findings from the questionnaires. Furthermore, data from school policy documents were analyzed to examine the role of the institution in promoting tolerance. Data validation was carried out through method triangulation, member checking, and peer debriefing. The research findings indicate that the practice of tolerance at SDI Logo is effective, particularly through interactions between students from different religious backgrounds. Tolerance does not arise spontaneously but is an integral part of the school culture, upheld through institutional policies and practiced in learning activities both inside and outside the classroom. This study can serve as a model for the implementation of tolerance in schools.